PENGARUH PRODUKTIVITAS KERJA DAN PRESTASI KERJA TERHADAP PEMBERIAN INSENTIF PEGAWAI DI DINAS TENAGA KERJA KABUPATEN KUTAI BARAT - Kusmirna, Ety - (EKONOMIA, 2018)
Ety Kusmirna, the effect of work productivity and work performance against employee incentives in the West Kutai District Labor Departement, Robin Jonathan and Mardiana.This study aims to determine the workplace and work performance of influence on employee incentives in the West Kutai District Power Office.The research population used by researches is all employees in the West Kutai District Labor Departement. The research team of 30 respondents and sampling determined is census (saturated sampling). Data analysis using multiple liniear regression with research instrument research and classical assumption test and hypothesis testing.The basis of theory of human resources focusing at productivity and work achievement has a significant effect on the administration of employeincentives in the West Kutai District Labor Departement.The result of the study concluded that : 1) H1 (hypothesis 1) received then meaningful productivity of a significant effect on the incentive gift. 2) The result showed that H2 ( hypothesis 2) received then means working performance has significant effect in the incentives gifts. 3) The results showed that H3 (hypothesis 3) received then meaningful work pride and performance achievement simultaneously significantly effect the incentives administration.